2014
DOI: 10.1007/s11136-014-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing responsiveness of the EQ-5D-5L, EQ-5D-3L and EQ VAS in stroke patients

Abstract: AimsTo date, evidence to support the construct validity of the EQ-5D-5L has primarily focused on cross-sectional data. The aims of this study were to examine the responsiveness of EQ-5D-5L in patients with stroke and to compare it with responsiveness of EQ-5D-3L and visual analogue scale (EQ VAS).MethodsWe performed an observational longitudinal cohort study of patients with stroke. At 1 week and 4 months post-stroke, patients were assessed with modified Rankin Scale (mRS) and Barthel Index (BI) and were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 34 publications
7
97
1
Order By: Relevance
“…For the worsened group, the SES of the EQ-5D-5L index were considered small (-0.29) but that of the EQ-VAS considered large (-0.82). Compared to a study in stroke patients [16], they found that SES of EQ-5D-5L index and EQ-VAS were medium (0.51-0.71) in patients with clinical improvement and small [-0.13 to (-0.45)] for the deteriorated group. This conflicts with our results that the EQ-5D-5L index was less responsive in the improved group, but the EQ-VAS was more responsive in the worsened group.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…For the worsened group, the SES of the EQ-5D-5L index were considered small (-0.29) but that of the EQ-VAS considered large (-0.82). Compared to a study in stroke patients [16], they found that SES of EQ-5D-5L index and EQ-VAS were medium (0.51-0.71) in patients with clinical improvement and small [-0.13 to (-0.45)] for the deteriorated group. This conflicts with our results that the EQ-5D-5L index was less responsive in the improved group, but the EQ-VAS was more responsive in the worsened group.…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies have shown that the EQ-5D-5L has good psychometric properties [12][13][14][15][16][17][18][19]. These studies were conducted in both general populations [12,13] and patient groups including cancer [14], hepatitis [15], stroke [16,17], Parkinson's disease [18], and HIV/AIDS [19]. Only one study was conducted in general population with chronic diseases [20].…”
Section: Introductionmentioning
confidence: 99%
“…We are limited by the lack of UK studies that use the newest version of the EQ-5D (5 level version as used in this study) when putting this figure into context. Data from the USA shows patients with COPD to have an index score of 0.79 21 and European data showed a score of 0.69 in patients 4 months after a stroke 22 Hence, our study would suggest that CRS does impact on quality of life and perhaps surprisingly to similar scale as that seen in other chronic disease states.…”
Section: Resultssupporting
confidence: 55%
“…Eleven studies (8%) employed the EQ-5D-5L [46,65,88,97,77,81,82,130,164,160,165]. No articles reported results on the youth version of the questionnaire (EQ-5D-Y), possibly because the validation process of the CEE national language versions was only completed in May 2015.…”
Section: Eq-5d Results: Versions Of Questionnaire Methods Of Reportimentioning
confidence: 99%
“…These were conducted in Bulgaria (n=1), Hungary (n=4), Poland (n=6) and Slovenia (n=3). Among these, we found representative population norms from Hungary, Poland and Slovenia [11,136,149,115,164,180]. Further, local population norm is available for the city of Burgas in Bulgaria [59].…”
Section: Population Normsmentioning
confidence: 99%